Influence of players` physical performances on the variation of the external and internal responses to repeated bouts of small-sided games across youth age categories - Castillo, D.; Yanci, J.; Raya-González, J.; Lago-Rodríguez, Á. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
The aim of this study was twofold: (1) to test for differences on the external and internal responses encountered by youth soccer players during four bouts of 5-a-side small-sided game (SSG) across age categories and, (2) to analyze the external and internal responses attending to players` sprinting and jumping profile within each age-category (i.e. under 14 (U14), under 16 (U16) and under 18 (U18)). Forty-eight young soccer players participated in this study and were distributed by each age-category. Players were classified based on jumping-profile (stronger and weaker) and sprint-profile (faster and slower). Also, players played four bouts of 4 min of a 5-a-side SSG, including goalkeepers. Likewise, external responses (i.e. total distance, distance covered at walking, jogging and high-intensity speeds, number of accelerations and decelerations, body impacts and player load) and internal responses (peak heart rate, % of peak heart rate and training impulse) were collected. The main results revealed a significant age-category by bout interaction for total distance covered, distance at jogging, number of accelerations, body impacts and player load for players from the U16 and U18 age categories, showing lower values during the last bouts, compared to the first bouts (p = 0.001-0.020, ?2p = 0.13-0.17). Moreover, while no significant (p = 0.09-0.95) sprint-profile by bout interaction was found for the registered variables across age categories, stronger U18 players showed a smaller decrease across bouts for distance covered at high-intensity, compared to weaker U18 players. These findings suggest there is a need for coaching staff to include training strategies that allow for reducing accumulated neuromuscular fatigue in U16 and U18 age categories.